2021
DOI: 10.3389/fpsyg.2021.647586
|View full text |Cite
|
Sign up to set email alerts
|

Do Islanders Have a More Reactive Behavioral Immune System? Social Cognitions and Preferred Interpersonal Distances During the COVID-19 Pandemic

Abstract: Insular populations have traditionally drawn a lot of attention from epidemiologists as they provide important insights regarding transmission of infectious diseases and propagation of epidemics. There are numerous historical instances where isolated populations showed high morbidity once a new virus entered the population. Building upon that and recent findings that the activation of the behavioral immune system (BIS) depends both upon one’s vulnerability and environmental context, we predicted that, during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 63 publications
4
13
1
Order By: Relevance
“…Analyses for the moderating role of the perceived threat of COVID-19 showed that this kind of threat played no role in the relationship between sexual disgust and homonegativity. Situational circumstances, such as a pandemic, are thought to strengthen the potential effects of disease-avoidance mechanisms (e.g., Bacon and Corr, 2020;Millar et al, 2020;Sorokowski et al, 2020;Hromatko et al, 2021;Miłkowska et al, 2021;Stevenson et al, 2021). Our research indicates, however, that concerns about COVID-19 have no effect on attitudes toward gay persons.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Analyses for the moderating role of the perceived threat of COVID-19 showed that this kind of threat played no role in the relationship between sexual disgust and homonegativity. Situational circumstances, such as a pandemic, are thought to strengthen the potential effects of disease-avoidance mechanisms (e.g., Bacon and Corr, 2020;Millar et al, 2020;Sorokowski et al, 2020;Hromatko et al, 2021;Miłkowska et al, 2021;Stevenson et al, 2021). Our research indicates, however, that concerns about COVID-19 have no effect on attitudes toward gay persons.…”
Section: Discussioncontrasting
confidence: 50%
“…Disease avoidance mechanisms and their potential role in explaining social attitudes have recently received much scientific attention (e.g., Mentser and Nussinson, 2020;Kramer and Bressan, 2021). In the context of the ongoing COVID-19 pandemic, they have become even more pertinent (Bressan, 2020;Seitz et al, 2020;Hromatko et al, 2021). Our study was designed to test the predictions emerging from the behavioral immune system theory (Ackerman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Polish women reported higher levels of disgust sensitivity during the COVID-19 pandemic than during the pre-pandemic period (Miłkowska et al, 2021). Also, Croatians scored higher on PVD and pathogen disgust, as well as preferred greater interpersonal distances during the pandemic comparing to pre-pandemic samples, especially when living on the islands (Hromatko et al, 2021). Apparently, a highly salient disease threat (such as during a pan demic) has the power to increase the intensity of germ aversion and disgust sensitivity (see also Stevenson et al, 2021).…”
Section: Functional Flexibility Of the Bismentioning
confidence: 92%
“…During the COVID-19 pandemic, topics of negative attitudes toward outgroups and the related social distancing tendencies have become important issues among scientists (e.g., Hromatko et al, 2021;Kramer & Bressan, 2021;Meleady et al, 2021;Sorokowski et al, 2020). One of the reasons for this intensified scientific interest is that social distancing, as well as the various factors that precede it, such as prejudices or xenophobic attitudes, have their origin in the perception of threat (Faulkner et al, 2004).…”
mentioning
confidence: 99%
“…), and unrealistic optimism may be contributing to poor decision making in many of these individuals. On the other side, one study has found that islandic, Croatian men scored higher on perceptions of infectability during the COVID-19 pandemic than before, while women did not, and the authors hypothesize that it may reflect the objectively higher risk of COVID-19 (Hromatko et al, 2021). This seems to suggest that at least some amount of increased personal risk for infection is acknowledged by higher-risk individuals during the current pandemic.…”
Section: Perceived Risk and Compliance With State Law And Public Health Recommendationsmentioning
confidence: 99%